HLA class I alleles and responsiveness of melanoma to immunotherapy with interferonalpha (IFN-α) and interleukin-2 (IL-2) - Scheibenbogen, Carmen; Keilholz, Ulrich; Mytilineos, Joannis; Suciu, S.; Manasterski, Maria; Hunstein, Werner (Melanoma research, 1994)
MHC-restricted recognition of melanoma cells by cytotoxic T lymphocytes is an important mechanism in vitro. Several HLA alleles can function as restriction elements for melanoma cell recognition. In this study we investigated whether there is a correlation between responsiveness of patients with metastatic melanoma (MM) to immunotherapy and the HLA type of the patient. Seventy-two patients received immunotherapy with IFN-a and IL-2 according to two different schedules with an overall response rate of 24%. In 54 patients, including 16 responders and 16 patients with stable disease, in whom peripheral blood lymphocytes were available, we determined HLA haplotypes. As a control group we prospectively determined HLA types in 67 melanoma patients of all stages who underwent surgery or received chemotherapy and of 126 healthy donors from our blood bank. Two HLA alleles that have been shown to function as restriction elements in vitro were observed more frequently in responding patients, namely Cw7 (p=0.014) and A1 (p=0.19). No association was found for A2 and B44. These observations provide evidence that the responsiveness of MM to immunotherapy with IL-2 is associated with certain HLA types, suggesting an important role of HLArestricted T lymphocytes for IL-2-induced tumour regression
Gesehen am 03.12.2025